PENGUATAN MODERASI BERAGAMA MELALUI SOLIDARITAS LOKAL PADA LEMBAGA PENDIDIKAN - Yunus Bayu; Romenah Romenah (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
This study aims to analyze the implementation and implications of Religious Moderation in the context of Islamic Religious Education (PAI) in State Vocational High Schools (SMK) in Tana Toraja Regency. Qualitative research using a pedagogical approach. The data sources in the study came from interviews, while the interviewed parties were, While secondary data were taken from documents related to the research. The results of the study indicate that religious moderation in the environment of Tana Toraja State Vocational High Schools has been formed indirectly (implicitly) and firmly. This is evidenced by the existence of respect for individual rights in religion, where there is no coercion, as well as the existence of strong tolerance practices that are harmoniously interwoven across various lines, from the family, school, to the community. A key factor supporting the successful implementation of religious moderation in PAI learning at Tana Toraja State Vocational High Schools is the strong accommodation of local wisdom of the local community. This local wisdom significantly influences and is integrated into the curriculum of educational institutions. In addition, the high level of social solidarity between religious communities in Toraja is also a supporting pillar. Thus, religious moderation indirectly has positive implications for Islamic religious education at Tana Toraja Regency State Vocational High Schools, reinforcing inclusive and harmonious values ​​in students' character development.